Experimental reduction in dietary omega-3 polyunsaturated fatty acids depresses sperm competitiveness - Rahman, Md. Moshiur (The Royal Society, 2014)
The health benefits of diets containing rich sources of long-chain omega-3 polyunsaturated fatty acids (n-3 LC-PUFA) are well documented and include reductions in the risk of several diseases typical of Western societies. The dietary intake of n-3 LC-PUFA has also been linked to fertility, and there is abundant evidence that a range of ejaculate traits linked to fertility in humans, livestock and other animals depend on an adequate intake of n-3 LC-PUFA from dietary sources. However, relatively few studies have explored how n-3 LC-PUFA influence reproductive fitness, particularly in the context of sexual selection. Here, we show that experimental reduction in the level of n-3 LC-PUFA in the diet of guppies (Poecilia reticulata) depresses a male's share of paternity when sperm compete for fertilization, confirming that the currently observed trend for reduced n-3 LC-PUFA in western diets has important implications for individual reproductive fitness.